PENGUKURAN KEPUASAN PENGGUNA DAN PENINGKATAN LAYANAN AKADEMIK ONLINE DI UNIVERSITAS MAJALENGKA - Abdurahman, Dede; Sopiandi, II (Teknik Informatika, Institut Teknologi Nasional malang, 2018)
The development of Information and Communication Technology penetrated to various aspects, not only in the field of business oriented, but also in the areas of government and education. Similar to other fields, in the field of education, Information and Communication Technology is one of the main needs for quality education. This study is an analytical survey to measure the level of satisfaction of SIMAK or web-based online application. Methods of data collection by spreading questionnaires to respondents or students as users of academic services at Majalengka University. The research models and instruments are based on the Customer Information Satisfaction (CIS) model, where after selection and testing the five dimensions of measurement are customer service, security, ease of use, information content, and innovation. Furthermore, based on these 5 dimensions composed an instrument or attribute measurement consisting of 15 questions.